RANKING TRAVEL AND TOURISM ENABLERS IN INDIA USING A FUZZY APPROACH - KUNAL GANGULY; Sidharth Rai (ASEAN Journal on Hospitality and Tourism, 2017)
This paper seeks to review the enablers for the Travel & Tourism (T&T) industry in India and to rank these factors. The paper aims to introduce a fuzzy TOPSIS approach for this purpose. The paper begins with a literature review to investigate the significant enablers in the T&T sector. The research was conducted among the tourists in the northern state of Uttarakhand, India which is a famous tourist destination both for adventure and pilgrimage. Fuzzy TOPSIS approach is used to meet the objectives of the study. Required information was gathered through a questionnaire. The results show that Safety & Security, Price, Transport and Infrastructure are the most important factors in Indian context.The paper will be helpful in enabling the T&T industry policy makers to identify the key service factors in the sector and take the improvement measuresThe concept of ranking T&T enablers using a Fuzzy TOPSIS is a new approach. The study is the unique application of a fuzzy approach to examine and rank customer expectations of the T&T enablers in Indian context.